Englacial Architecture and Age‐Depth Constraints Across the West Antarctic Ice Sheet. Issue 6 (10th March 2020) - Ashmore, David W.; Bingham, Robert G.; Ross, Neil; Siegert, Martin J.; Jordan, Tom A.; Mair, Douglas W. F.
Abstract: The englacial stratigraphic architecture of internal reflection horizons (IRHs) as imaged by ice‐penetrating radar (IPR) across ice sheets reflects the cumulative effects of surface mass balance, basal melt, and ice flow. IRHs, considered isochrones, have typically been traced in interior, slow‐flowing regions. Here, we identify three distinctive IRHs spanning the Institute and Möller catchments that cover 50% of West Antarctica's Weddell Sea Sector and are characterized by a complex system of ice stream tributaries. We place age constraints on IRHs through their intersections with previous geophysical surveys tied to Byrd Ice Core and by age‐depth modeling. We further show where the oldest ice likely exists within the region and that Holocene ice‐dynamic changes were limited to the catchment's lower reaches. The traced IRHs from this study have clear potential to nucleate a wider continental‐scale IRH database for validating ice sheet models. Plain Language Summary: Ice‐penetrating radar is widely used to measure the thickness of ice sheets, critical to assessments of global sea level rise potential. This technique also captures reflections from chemical contrasts within the ice sheet, caused by the atmospheric deposition of conductive impurities, known as "internal reflection horizons" (IRHs) that can be traced over large distances. As these deposits are laid down in distinct events, most IRHs are isochronous age tracers and contain valuable information on past ice sheet processes. In this paper we trace and place age constraints on stratigraphic horizons across a large portion of the West Antarctic Ice Sheet, including regions where fast ice flow has disrupted the ice sheet stratigraphy. The resulting data set allows us to identify where the oldest ice is buried in the study region and provides evidence that flow of the ice sheet interior has been stable during the Holocene. Our results can be used to test the performance of ice sheet models, which seek to simulate the response of ice sheets to long‐term environmental change. Key Points: We measure and date individual isochronal radar internal reflection horizons across the Weddell Sea sector of the West Antarctic Ice Sheet Horizons dated to 1.9–3.2, 3.5–6.0, and 4.6–8.1 ka are widespread and linked to previous radar surveys of the Ross and Amundsen Sea sectors These form the basis for a wider database of ice sheet architecture for validating and calibrating ice sheet models of West Antarctica